Determinants of Uptake of Cervical Cancer Screening among Women Attending Tertiary Level Hospital - Ghimire, Bijaya; Pathak, Pratima (Journal of Nepal Health Research Council, 2021)
Background: Cervical cancer, being the fourth commonest cancer in women worldwide, is also the most frequent cause of cancer deaths among women in developing and underdeveloped countries. Screening is the gold standard to control the disease yet, its uptake is still very low among Nepalese women. Thus, the objective of this study was to find out the determinants of uptake of cervical cancer screening among women. Methods: Data were collected from a total of 220 women visiting gynecology outpatient department of Tribhuvan University Teaching Hospital, Kathmandu by using non-probability purposive sampling technique. Descriptive statistics and binary logistic regression analysis were applied. Results: The study findings revealed that the prevalence of uptake of cervical cancer screening was about one third (38.6%). Educational qualification had a significant association with the uptake of cervical cancer screening (p=0.017). Women’s age (COR=0.267; 95%CI=0.150-0.475), knowledge on availability of health services (COR=5.310; 95% CI=2.947-9.567), awareness on cost of screening services (COR=26.329; 95% CI=12.704-54.566), and knowledge level (COR=2.677; 95%CI= 1.385-5.173) had a significant association with the uptake of cervical cancer screening in bivariate analysis. Age (AOR=0.148; 95%CI=0.058-0.375) and awareness on cost of screening services (AOR=61.048, 95%CI=19.194-194.175) were found as major determinants of uptake of cervical cancer screening. Conclusions: The findings of this study conclude that the prevalence of uptake of cervical cancer screening was below half. Determinants of uptake of cervical cancer screening were age and awareness on the cost of screening services. So, awareness campaigns about cervical cancer screening are very necessary to increase its uptake and to reduce the morbidity and mortality associated with it. Keywords: Cervical cancer screening; determinants; uptake